Introduction: The mobile landscape of post-war architectural thought - Agarez, R.; Heynickx, R.; Couchez, Elke (Architecture thinking across boundaries: Knowledge transfers since the 1960s, 2021)
Around 1908, the German sociologist Georg Simmel reflected on the significance of mobility infrastructures, such as paths and bridges. These divisions of space, he wrote, were more than physical facts. They resulted from a subjective understanding of space, namely the human will to link distinct elements. Boundaries, paths and bridges were creations of a human being, the ‘connecting creature who must always separate and who cannot connect without separating’. Simmel called this double act of separation and connection, resulting in a dynamic intertwining of physical place and mental spaces, the ‘miracle of the road’ (Simmel [1909] in Leach 1997: 64–7).